2001
DOI: 10.1111/1467-8624.00285
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Patterns of Time Use in Adolescence

Abstract: Patterns of time use are tangible representations of individual identity and the meaning of age groups in the life course. How do young people allocate their time to multiple domains of involvement, including the school, workplace, family, and peer group? Drawing on longitudinal data from the Youth Development Study (N = 1,010), a person-centered analytic strategy was used to describe configurations of time use through the high school years. Over half of the students were engaged in many domains, although a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
107
0
6

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 52 publications
7
107
0
6
Order By: Relevance
“…Even though the shape of the trajectories was not the same, both showed a decline towards the end of high school. Given the likely changes in autonomy, identity exploration, time allocation, and opportunities for involvement during the course of adolescence (Barber et al, 2005;McNeal, 1998;Pedersen, 2005;Shanahan & Flaherty, 2001), this decline was expected for a majority of youth. As put forward in the introduction, participation in organized activities may be rooted in these developmental processes.…”
Section: Intensity and Breadth Of Participation Over Timementioning
confidence: 99%
See 2 more Smart Citations
“…Even though the shape of the trajectories was not the same, both showed a decline towards the end of high school. Given the likely changes in autonomy, identity exploration, time allocation, and opportunities for involvement during the course of adolescence (Barber et al, 2005;McNeal, 1998;Pedersen, 2005;Shanahan & Flaherty, 2001), this decline was expected for a majority of youth. As put forward in the introduction, participation in organized activities may be rooted in these developmental processes.…”
Section: Intensity and Breadth Of Participation Over Timementioning
confidence: 99%
“…Along with this transition, organized activities are likely to become salient in their lives. These activities are usually offered at younger ages, but discretionary time increases in early adolescence and youth are faced with a wider range of opportunities both in and out of school (Shanahan & Flaherty, 2001). From a developmental perspective, as proposed by Eccles and Gootman (2002), we believe that organized activities may help youth navigate through the developmental tasks of adolescence, especially those related to autonomy and identity.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Today, secondary and postsecondary education credentials are more important than ever before (Schoon & Parsons, 2002). Nevertheless, adolescents in North America are likely to combine secondary school attendance and employment, not to trade off one against the other (Shanahan & Flaherty, 2001). A large majority of U.S. high school students are employed at least some time while school is in session (Committee on the Health and Safety Implications of Child Labor, 1998).…”
Section: The Contemporary Context Of Adolescent Workmentioning
confidence: 99%
“…Using YDS data and cluster analysis to identify groups of adolescents with common patterns of time use, Shanahan and Flaherty (2001) found that there was little trading of paid work time for time doing schoolwork. In their study, two clusters of young people emerged who were actively involved in diverse activities.…”
Section: The Contemporary Context Of Adolescent Workmentioning
confidence: 99%